E-GOVERNMENT SUCCESS FACTORS FROM A BUSINESSES PERSPECTIVE IN DEVELOPING COUNTRIES: A CASE OF JORDAN - Kanaan, AnasGhassan; Hassan, Shahizan Bin (International Journal of Research -GRANTHAALAYAH, 2016)
This paper presents a study which examines several e-government success factors in Jordan. Due to the pace of globalization and rapid global growth of technology and the Internet information, many governments around the world have turned their services from traditional services into e-government services. Were the citizens, business organizations and other stakeholders are served via the internet. Jordan is one of the rare countries in the Middle East with a history of commitment to good governance and ICT-related initiatives. In recent years, Jordan’s efforts to provide e-government services to the public have been recognized. But still Jordan faces the problem of low usage levels of these electronic services, plus several scholars addressed that several studies were conducted from citizen perspective but few for businesses perspective. For a better understanding of e-government and its influence on the society as all and on the business society in particular the researchers carried out this study to identify the success factors which affect e-government adoption in Jordan, also to investigate the factors that determine business organization satisfaction towards e-government in Jordan. In this paper the researcher will discuss four factors that affect the success of e-government services from businesses perspective in Jordan as followed: e-service quality, perceived usefulness, trust, personalization.